Or telle his tale untrewe : an enquiry into a narrative strategy in the Canterbury Tales - Chaskalson, Lorraine (My University, 2015)
In this thesis I discuss aspects of Chaucer's interest in the relation of Language to the reality which it attempts to express and the relation of poetic fiction to Christian truth, and the type of readerly response invited by this interest. The method employed includes analysis of the structural development of the narrative frame and, to a lesser degree, of the entirety of the poem, as well as discussion of the historical context of the issues under consideration. These issues are raised in the narrative frame of the Canterbury Tales and are explored there and in the individual tales. Their treatment in the narrative frame is seminal and has provided the major focus of discussion in what follows. The narrative frame structure operates dually. In the diachrony of a first reading of the poem, the frame world provides a correlative to the actual world in which man experiences serial time. The realignments of interpretation necessary because of its changing claims regarding its own nature — and hence its changing demands upon its readers — are constant reminders of the relativity of human judgment and experience in space and time. "rn the synchrony inevitable in a second or subsequent Lng, which comprehends the entirety of the poem at each point in its linear progression, the reader's position outside the poem's time span of past, present and future, is analogous to the poet’s in his original conception of the poem and to God's in relation to the actual world, which the poem's world imitates. After a first reading the reader sees that initially Chaucer's truth claim has enabled him to trust the authenticity of the account and to regard it not as poetic invention but as a report of historical truth.
Keywords: Chaucer, Geoffrey, 1400.--Canterbury tales; Narration (Rhetoric); Tales, Medieval--History and criticism